2016
DOI: 10.18632/oncotarget.14373
|View full text |Cite
|
Sign up to set email alerts
|

Targeting P-glycoprotein function, p53 and energy metabolism: Combination of metformin and 2-deoxyglucose reverses the multidrug resistance of MCF-7/Dox cells to doxorubicin

Abstract: Multidrug resistance(MDR) is a major obstacle to efficiency of breast cancer chemotherapy. We investigated whether combination of metformin and 2-deoxyglucose reverses MDR of MCF-7/Dox cells and tried to elucidate the possible mechanisms. The combination of metformin and 2-deoxyglucose selectively enhanced cytotoxicity of doxorubicin against MCF-7/Dox cells. Combination of the two drugs resumed p53 function via inhibiting overexpression of murine doubleminute 2(MDM2) and murine doubleminute 4(MDM4) leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Recent studies have shown that metformin exerts multiple antitumor effects in vivo and in vitro . However, these antitumor effects as well as the related underlying mechanisms vary among different cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that metformin exerts multiple antitumor effects in vivo and in vitro . However, these antitumor effects as well as the related underlying mechanisms vary among different cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that metformin exerts multiple antitumor effects in vivo and in vitro. (24)(25)(26) However, these antitumor effects as well as the related underlying mechanisms vary among different cancer cells. In colorectal cancer, metformin suppresses colonic epithelial proliferation by inhibiting the mTOR pathway via AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…All of cell lines were kept in the incubator at 37°C with 5% CO 2 and 95% humidity. Maintenance of cell resistance refers to previous description (Xue et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…Lately, several studies have reported that metformin not only inhibits cell proliferation in breast, gastric, ovarian, and small cell lung cancers [8][9][10][11] but also potentiates the cytotoxic effect of some TKIs in bladder, colorectal, and non-small cell lung cancer [12][13][14]. In addition, it is also known to reverse multidrug resistance by regulating cancer stem cell population or signaling [15][16][17]. However, the effects of metformin on CML have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%